The international financial crisis: Theoretical debates, economic policies, and lessons - Santarcángelo, Juan E. (2013)
The global financial crisis has had a strong impact on most European countries. While at first the massive injection of resources helped the financial system not to collapse, the austerity policies implemented throughout the continent have not brought the expected economic growth. Interestingly, the type of intervention undertaken is rooted in the neoclassical tradition, which entails a specific understanding of the functioning of the financial system and the economy. In this context, the objectives of this paper are firstly, to analyze the main theoretical assumptions and the specific way in which the crisis is understood and the applied economic policies are developed under this tradition; and secondly, to account for the social and economic impact of the policies applied, and the different margins of action that each European country still has.